Network Governance Dynamics in Zero-Burning Land Management Policy: Lessons from South Sumatra - Ujang Alnema; Alfitri Alfitri; Raniasa Putra; Abdul Nadjib (Eduvest - Journal of Universal Studies, 2026)
Forest and land fires remain a persistent environmental challenge in South Sumatra, Indonesia, despite the implementation of the Zero-Burning Land Management Policy. This study examines the dynamics of network governance in the implementation of the policy by integrating Social Network Analysis (SNA) and in-depth interviews within a mixed-method framework. The research aims to analyze the structure of governance networks, coordination mechanisms, conflict and power dynamics, and adaptive responses among key actors, including provincial and district governments, plantation companies, NGOs, and local communities. The findings reveal a moderately centralized governance structure, with the provincial government acting as the dominant coordinating entity. While the network exhibits characteristics of a lead organization model, horizontal collaboration—especially in operational coordination—is also evident. Formal mechanisms such as inter-agency meetings and integrated task forces are complemented by informal coordination based on trust and personal relationships. However, the network is influenced by unequal capacities, resource imbalances, and overlapping authorities, which affect the stability and effectiveness of collaboration. The research also identifies adaptive responses, including the formation of integrated task forces, technology-based fire monitoring systems, and adjustments to local regulations. While these responses demonstrate institutional flexibility, adaptation remains largely reactive to crises rather than being integrated into systematic learning processes. Theoretically, the findings contribute to adaptive network governance by highlighting the interdependence of network structure, coordination quality, and adaptive capacity in environmental policy. For developing countries facing ecological pressures, strengthening trust, data integration, and institutional continuity is key to improving policy resilience and long-term fire prevention effectiveness.